Biophysical Characterization of the Recombinant Importin-alpha from Neurospora crassa - Takeda, Agnes A. S. [UNESP]; Freitas, Fernanda Zanolli [UNESP]; Magro, Angelo J. [UNESP]; Bernardes, Natalia E. [UNESP]; Fernandes, Carlos A. H. [UNESP]; Goncalves, Rodrigo D. [UNESP]; Bertolini, Maria Celia [UNESP]; Fontes, Marcos R. M. [UNESP] (Bentham Science Publ Ltd, 2013)
Neurospora crassa has been widely used as a model organism and contributed to the development of biochemistry and molecular biology by allowing the identification of many metabolic pathways and mechanisms responsible for gene regulation. Nuclear proteins are synthesized in the cytoplasm and need to be translocated to the nucleus to exert their functions which the importin alpha-receptor has a key role for the classical nuclear import pathway. In an attempt to get structural information of the nuclear transport process in N. crassa, we present herein the cloning, expression, purification and structural studies with N-terminally truncated IMP alpha from N. crassa (IMP alpha-Nc). Circular dichroism analysis revealed that the IMP alpha-Nc obtained is correctly folded and presents a high structural conservation compared to other importins-alpha. Dynamic light scattering, analytical size-exclusion chromatography experiments and molecular dynamics simulations indicated that the IMP alpha-Nc unbound to any ligand may present low stability in solution. The IMP alpha-Nc theoretical model displayed high similarity of its inner concave surface, which binds the cargo proteins containing the nuclear localization sequences, among IMP alpha from different species. However, the presence of non-conserved amino acids relatively close to the NLS binding region may influence the binding specificity of IMP alpha-Nc to cargo proteins.
Keywords: Biophysical characterization; classical nuclear import pathway; heterologous expression; homology modeling; importin-alpha; Neurospora crassa